Acquisition of fast transient signals in ICP-MS with enhanced time resolution. Issue 8 (8th July 2016) - Managh, Amy J.; Douglas, David N.; Makella Cowen, K.; Reid, Helen J.; Sharp, Barry L.
Abstract : Improving time resolution in sector-field ICP-MS through use of a plug-in data acquisition board. Abstract : In recent years, the field of ICP-MS has seen an increasing trend towards sampling systems and methods that produce short transient signals, rather than a continuous signal response. Fast data acquisition, readout and storage are crucial to take advantage of the wealth of information available from these approaches. However, many of the current generation mass spectrometers, in particular sector-field instruments, were not designed to cope with such short duration signals. This article reports the use of a commercially available multi-channel scaler board, which facilitates capture of TTL pulses from an ICP-MS detector at a user defined time resolution down to 100 ns. The board was used to profile 400–600 μs wide signals with 10 μs resolution, derived from the nebulisation of a 50 nm gold nanoparticle suspension. Furthermore, the benefit of a 100% duty cycle was demonstrated for ∼10 ms wide signals, following ablation of individual macrophage cells with a fast response LA-ICP-MS interface.